2023
DOI: 10.3390/antibiotics12101481
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of New β-Lactamase Inhibitor Combinations against blaNDM, blaKPC, and ESBL-Producing Enterobacteriales Uropathogens

Lubna Razaq,
Fakhur Uddin,
Shahzad Ali
et al.

Abstract: Antibiotic resistance in uropathogens has increased substantially and severely affected treatment of urinary tract infections (UTIs). Lately, some new formulations, including meropenem/vaborbactam (MEV), ceftazidime/avibactam (CZA), and ceftolozane/tazobactam (C/T) have been introduced to treat infections caused by drug-resistant pathogens. This study was designed to screen Enterobacteriales isolates from UTI patients and to assess their antimicrobial resistance pattern, particularly against the mentioned (new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Furthermore, it is desirable to support genotypic tests, such as DNA microarray and PCR, for the study of resistance mechanisms, mostly present in isolates at a local level, which can improve the understanding of the molecular mechanisms underlying antibiotic resistance [ 24 ]. In Pakistan, Uddin et al reported a high prevalence of K. pneumoniae MDR, of which 98% were ESBL producers; furthermore, NDM-positive isolates were resistant to newer formulations, including meropenem/vaborbactam (MEV), ceftazidime/avibactam (CZA), and ceftolozane/tazobactam (C/T) [ 25 , 26 ]. In Saudi Arabia, surveillance of K. pneumoniae antibiotic resistance revealed an increased rate of resistance among different classes of antibiotics [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is desirable to support genotypic tests, such as DNA microarray and PCR, for the study of resistance mechanisms, mostly present in isolates at a local level, which can improve the understanding of the molecular mechanisms underlying antibiotic resistance [ 24 ]. In Pakistan, Uddin et al reported a high prevalence of K. pneumoniae MDR, of which 98% were ESBL producers; furthermore, NDM-positive isolates were resistant to newer formulations, including meropenem/vaborbactam (MEV), ceftazidime/avibactam (CZA), and ceftolozane/tazobactam (C/T) [ 25 , 26 ]. In Saudi Arabia, surveillance of K. pneumoniae antibiotic resistance revealed an increased rate of resistance among different classes of antibiotics [ 27 ].…”
Section: Introductionmentioning
confidence: 99%